Kidney and Liver Injuries After Major Burns in Rats Are Prevented by Resolvin D2. Issue 5 (May 2016) - Inoue, Yoshitaka; Yu, Yong-Ming; Kurihara, Tomohiro; Vasilyev, Aleksandr; Ibrahim, Amir; Oklu, Rahmi; Zhao, Gaofeng; Nair, Anil V.; Brown, Dennis; Fischman, Alan J.; Tompkins, Ronald G.; Irimia, Daniel
Abstract : Objectives: Innate immune dysfunction after major burn injuries increases the susceptibility to organ failure. Lipid mediators of inflammation resolution, e.g., resolvin D2, have been shown recently to restore neutrophil functionality and reduce mortality rate in a rat model of major burn injury. However, the physiological mechanisms responsible for the benefic activity of resolvin D2 are not well understood. Design: Prospective randomized animal investigation. Setting: Academic research setting. Subjects: Wistar male rats. Interventions: Animals were subjected to a full-thickness burn of 30% total body surface area. Two hours after burn, 25 ng/kg resolvin D2 was administered IV and repeated every day, for 8 days. At day 10 post burn, 2 mg/kg of lipopolysaccharide was administered IV, and the presence of renal and hepatic injuries was evaluated at day 11 post burn by histology, immunohistochemistry, and relevant blood chemistry. Measurements and Main Results: In untreated animals, we found significant tissue damage in the kidneys and liver, consistent with acute tubular necrosis and multifocal necrosis, and changes in blood chemistry, reflecting the deterioration of renal and hepatic functions. We detected less tissue damage and significantly lower values of blood urea nitrogen (26.4 ± 2.1 vs 36.0 ± 9.3 mg/dL; p ⩽ 0.001), alanine aminotransferase (266.5 ± 295.2 vs 861.8 ± 813.7 U/L; p ⩽ 0.01), and total bilirubin (0.13 ± 0.05 vs 0.30 ± 0.14 mg/dL; p ⩽ 0.01) in resolvin D2–treated rats than in untreated animals. The mean blood pressure of all animals was above 65 mm Hg, indicating adequate tissue perfusion throughout the experiments. We measured significantly larger amounts of chromatin in the circulation of untreated than of resolvin D2–treated rats (575.1 ± 331.0 vs 264.1 ± 122.4 ng/mL; p ⩽ 0.05) and identified neutrophil extracellular traps in kidney and liver tissues from untreated rats, consistent with the tissue damage. Conclusions: Pathologic changes in kidney and liver tissues in a rat model of major burn and endotoxin insults are ameliorated by resolvin D2.